A proposed mechanism to achieve digital empowerment in the Ministry of Education from the point of view of administrative leaders in the light of Corona crisis and its developments - الأشقر نادية (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aimed to identify the level of digital empowerment in the Ministry of Education in Jordan from the point of view of its administrative leaders in the light of Corona crisis and its developments and to develop a proposed mechanism to achieve this. The study sample consisted of (49) members of administrative leaders in the Ministry of Education and the directorates of education in the capital Amman, and the descriptive survey approach was followed to suit it for the purposes of the study. The digital infrastructure, awareness of the importance of digital empowerment, digital activities and evaluation methods, and its validity and reliability were verified and appropriate statistical methods used, and the results of the study showed the following: The level of digital empowerment in the Jordanian Ministry of Education was high from the point of view of the administrative leaders in it.